Aspects of choosing by applicants a secondary special or higher education institution - L. G. Akhmaeva; A. I. Eremeeva (Цифровая социология)
A brief overview of the modern system of secondary special and higher education in the Russian Federation has been given. The problem of competitiveness of educational institutions in the Russian Federation and the world in General has been raised. Statistical data conducted at the end of 2019 questionnaires among the students of the Department of Advertising and Public Relations the State University of Management (Moscow) and students of the Faculty of Advertising and Internet Communications, the International College of Arts and Communications (Moscow).The influence of several factors on the choice by learners of studying educational institutions has been explored, key factors for choice has been highlighted. The opinions of students in terms of the applicability of disciplines in their future profession, assessment of students of the faculty of the institution, the relevance of the cost of education quality and prospects for future employment in the profession after graduation have been analysed.According to the results of the survey, answers were given to such questions as: how do applicants themselves choose an educational program – their future profession? How do they perceive the educational service provided to them by the educational institution? How do applicants who have already become students evaluate their choice of educational institution, the quality of educational service and prospects for their future employment? What is necessary for the formation of demand for educational service?Based on the conducted sociological research, conclusions regarding the choice of educational institution by applicants have been made. The authors’ recommendations to educational institutions to attract applicants and increase their competitiveness in the market of educational services are given.